The road to sustainability in universities: The Case of The Autonomous University of Bucaramanga - Castro Hernández, Yohana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
UNAB, due to its social and environmental responsibility, formulated an environmental management system for all its headquarters in three stages: Participatory environmental diagnosis, through three methodologies: a perception survey, evaluation of environmental impacts, Arboleda method and review of the requirements legal; followed by the planning of actions, due to the analysis of risks and opportunities, structuring of the committee and programs and finally the guidelines for the implementation were formulated through the plan of registration, storage and communication of results. For the academic community, the current environmental management performs good management of waste and resources, highlighting the improvements in the transmission of knowledge to employees and students.